Analysis of Fishermen’s Catch Productivity in Lake Tempe, Wajo Regency, South Sulawesi - Nur Fadhilah Abustang; Syeiqido Sora Datu; Dewi Virgiastuti Jarir; suryo Wirawan Anton; Riswan Dugo (Jurnal Studi Perikanan Berkelanjutan, 2025)
Inland fisheries play a vital role in providing sources of animal protein, particularly in the Lake Tempe region, Wajo Regency, South Sulawesi. This study aims to analyze the productivity of fishermen’s catches and the factors influencing their variation. The research employed a field survey with a quantitative approach through the collection of primary data, including catch quantity, fishing gear type, and fishing effort. The study was conducted on April 12, 2025, involving 30 fishermen as respondents. Data were analyzed using the Catch per Unit Effort (CPUE) method and quantitative descriptive analysis. The results showed that the average CPUE of fishermen in Lake Tempe fluctuated, influenced by fishing gear type, environmental conditions, and fishing season. The highest CPUE was recorded for fishermen using traps (bubu), while the lowest was found among those using gillnets. These findings indicate significant differences in the effectiveness of fishing gear on catch productivity. Moreover, environmental factors such as local climate variation and fish stock availability also play a major role in determining productivity. The study’s results are expected to serve as input for sustainable fisheries management in Lake Tempe. Therefore, implementing environmentally friendly fishing gear and improving fishermen’s capacity in resource management are crucial. This study underscores that ecosystem-based and sustainable management approaches are essential to maintaining the livelihood of local fishing communities.